SYNTHESIS CATALYST Ni / STAND AND ITS APPLICATION PROCESSES HYDROGENATION OF OILS - Garrido-Schaeffer, A. (1999)
Nickel -based catalysts were prepared by impregnation and subsequent calcination at a concentration of 10 % by weight on the following substrates : clay , Ti02 , Si02 and Al 203 . These were reduced in a stream of 20 % hydrogen / nitrogen at a temperature of 350 ° C for 2 hours and were characterized by X-ray diffraction with activity measurements determined that the different supports affects performance . The increasing order of performance of the catalysts with different supports in oil hydrogenation process is as follows: clay > Ti02 > at 20 3> Si02 . Activity results show that the clay has a good performance in the hydrogenation process reaching iodine decrease of sunflower oil from 150 076 to the value of 56.77 to a temperature of 280 ° C